Nonmedical use of pain medications in dental patients. (July 2014) - Ashrafioun, Lisham; Edwards, Paul C.; Bohnert, Amy S. B.; Ilgen, Mark A.
Abstract Background: Substance use is overrepresented in dental clinics that provide affordable care and dental clinics provide potential access to opioid analgesics. Research is needed to better understand prescription opioid misuse in this population. Objective: The purpose of this study was to assess the prevalence and correlates of the misuse of prescription opioids in adults seeking dental care from a low-cost dental training clinic. Methods: Patients were recruited from a university school's dentistry patient emergency and admission services clinic. Patients (n = 369) within the waiting area of the clinic completed a self-report questionnaire about their nonmedical use of prescription pain medications, medication diversion and use of substances. Results: Approximately 37.9% (140/369) of those who completed the study survey reported at least some nonmedical use of pain medications within the past 30 days. Use was associated with diversion of medication, and use of tobacco, marijuana, and sedatives. Conclusions: Within this sample from a dental clinic, nonmedical use of prescription pain medications was more common than in the general population. This suggests that dental clinics may be an appropriate setting for provider education and patient-based intervention strategies to reduce nonmedical use of pain medications.